Pharmacognostical and phytochemical analysis Of Bhringraj (Eclipta Alba Hassk.) - Sharma, Ritu; Nathani, Sumit (International Research Journal of Ayurveda & Yoga, 2020)
Bhringraj (Eclipta alba Hassk.) is an annual herbaceous plant found throughout world during rainy season. It is indicated in krimi, kustha, switra, khalitya, palitya, kasa, swarbheda, darunaka and as rasayan in ayurveda texts. The herb is known for its property like hepatoprotective, antiviral, antibacterial, hypotensive, anti-leprotic, analgesic, antioxidant, anti-haemorrhagic, anticancer, anti-hepatotoxic, promoter for blackening and growth of hair. Evaluation of pharmacognostical and phytochemical standards including powder microscopy, physio-chemical parameters, phytochemical screening and thin layer chromatography were done for identification, authentication and standardization of drug. The phytochemical analysis shows presence of carbohydrates, alkaloids, proteins, tannins, saponin and phenols.